Pengaruh Beberapa Variabel Moneter Terhadap Harga Saham di Lima Negara Asean - Wulandari, Dwi (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198), 2015)
The purpose of this research is to understand the impact of  monetary variables namely inflation, interest rate, exchange rate and money supply on stock prices in five ASEAN countries namely Indonesia, Malaysia, Thailand, Philipinnes and Singapore. These countries has different characteristic than stock market in other countries because their stock market has experienced two big crises. Monetary policy of their government has serious impact on how these countries managed their financial markets.  It was found that there were different variables affecting stock price in these countries. In Indonesia, stock prices are affected by stock prices in the past. In Malaysia, stock prices are affected by exchange rate. While in Thailand, stock prices are affected by interest rate. In Philipinnes, stock prices are affected by interest rate and stock prices in the past. In Singapore, stock prices are affected by the inflation rate.
Keywords: stock price; inflation; interest rate; exchange rate; money supply; ASEAN countries